Continuous In Vivo Monitoring of Indole-3-Acetic Acid and Salicylic Acid in Tomato Leaf Veins Based on an Electrochemical Microsensor - Lingjuan Tang; Daodong Li; Wei Liu; Yafang Sun; Ying Dai; Wenjing Cui; Xinliu Geng; Dayong Li; Fengming Song; Lijun Sun (Biosensors, 2023)
Indole-3-acetic acid (IAA) and salicylic acid (SA), as critical plant hormones, are involved in multiple physiological regulatory processes of plants. Simultaneous and continuous in vivo detection of IAA and SA will help clarify the mechanisms of their regulation and crosstalk. First, this study reports the development and application of an electrochemical microsensor for simultaneous and continuous in vivo detection of IAA and SA. This electrochemical microsensor system consisted of a tip (length, 2 mm) of platinum wire (diameter, 0.1 mm) modified with carbon cement and multi-walled carbon nanotubes, an untreated tip (length, 2 mm) of platinum wire (diameter, 0.1 mm), as well as a tip (length, 2 mm) of Ag/AgCl wire (diameter, 0.1 mm). It was capable of detecting IAA in the level ranging from 0.1 to 30 µM and SA ranging from 0.1 to 50 µM based on the differential pulse voltammetry or amperometric i-t., respectively. The dynamics of IAA and SA levels in tomato leaf veins under high salinity stress were continuously detected in vivo, and very little damage occurred. Compared to conventional detection methods, the constructed microsensor is not only suitable for continuously detecting IAA and SA in microscopic plant tissue in vivo, it also reduces the damage done to plants during the detection. More importantly, the continuous and dynamic changes in IAA and SA data obtained in stiu through this system not only can help clarify the interaction mechanisms of IAA and SA in plants, it also helps to evaluate the health status of plants, which will promote the development of basic research in botany and precision agriculture.